Evaluating the National University of Lesotho’s Records Management practices with the ISO 15489 - Tankiso A. Thaanyane; Pheladi T. Lefika; Sithembiso Khumalo (South African Journal of Information Management)
Background: Universities create different types, categories and classes of records during their main activities which stem from learning, teaching, research and community engagement. The information contained in the records is used in the daily activities of an institution, therefore, they need to be arranged systematically to facilitate easy access and avoid loss of misfiling or damage.